Analyse multicritère pour le choix de site d'implantation d'une station d'épuration des eaux usées dans la commune de «Souk Ahras» - DJABALLAH ,Wissem; Dr. HADJI ,Riheb (Encadreur) (Université Ferhat Abbas Sétif 1. institut d'architecture et sciences de la terre. département de géologie, 2017)
The purpose of this work is to identify and map the areas most favorable to the implementation of a wastewater treatment plant in the region of souk ahras based on the integration in a GIS of products derived from a DTM, Remote sensing and land occupation. The proposed methodology is based on the analysis of the different themes involved in the selection of sites for a wastewater treatment plant: criteria related to mapping, urbanization, geological formations, etc. Finally, the criteria adopted are integrated into a multicriteria analysis. Favorable areas are concentrated in the Medjerda valley and in the north of the region.
الهدف من هذا العمل هو تحديد و رسم الخرائط للمناطق الأكثر ملاءمة لإنجاز محطات تصفية مياه الصرف الصحي في منطقة سوق أهراس بالاعتماد على إدراج نواتج النموذج الرقمي لسطح الأرض و التحسس عن بعد و شغل الأراضي داخل نظم المعلومات الجغرافية. المنهاجية لمقترحة تعتمد على تحليل مختلف العوامل المتدخلة في اختيار موقع محطة التصفية : معايير مرتبطة بالطبوغرافيا, التعمير و التشكيلات الجيولوجية. و في الأخير المعايير المعتمدة تم دمجها في عملية تحليل متعددة العوامل. المناطق الملاءمة تتركز في وادي مجردة وشمال لمنطقة
Keywords: Souk Ahras; SIG; Analyse Multicritères; Occupation de sol; MNT